2010
DOI: 10.1371/journal.pone.0010494
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection by Hepatitis C Virus in HIV-Infected Patients in Southern Brazil: Genotype Distribution and Clinical Correlates

Abstract: BackgroundPrevalence rates of Hepatitis C Virus (HCV) co-infection, the distribution of HCV genotypes, and the frequency of spontaneous resolution of hepatitis C in patients infected with the Human Immunodeficiency Virus (HIV) have a worldwide disparity. The purpose of this study is to investigate the prevalence of HCV antibodies (anti-HCV) in patients with HIV, the proportion and correlates of infection by different HCV genotypes, and rates of spontaneous resolution of HCV infection.MethodsA cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
6
23
8
Order By: Relevance
“…However, such findings have not been confirmed by other authors [24,[26][27][28][29][30][31][32][33][34][35][36][37][38]. In the present study, we also found no significant difference in SVR between patients who used PI or NNRTI, or even when NRTIs were individually evaluated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, such findings have not been confirmed by other authors [24,[26][27][28][29][30][31][32][33][34][35][36][37][38]. In the present study, we also found no significant difference in SVR between patients who used PI or NNRTI, or even when NRTIs were individually evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…These elevated SVR rates can be explained by the smaller proportion of genotype 1 patients (about 50%), while in the present study, this genotype represented more than 80% of the patients, which is in accordance with epidemiological data in our region [36].…”
Section: Discussionsupporting
confidence: 93%
“…12 Our results showed a prevalence of 23.6% of HIV-1/HCV coinfection, similar to previous findings in other HIV-1 Brazilian populations. 13,14 Between 20% and 30% of individuals monoinfected with HCV have spontaneous clearance of hepatitis C after the acute phase. 15 The rate of spontaneous resolution appears to be lower in patients coinfected with HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, outbreaks of HCV infections in health care settings due to contaminated medical equipment continue to occur, expanding epidemics of injection drug users (IDUs) and human immunodeficiency virus (HIV) infections in China . The high prevalence of HCV among IDUs and HIV‐infected individuals as well as the high prevalence of HCV and HIV coinfection among IDUs are also increasing . These data, in addition to the known efficiency of HCV transmission through injection, the popularity of therapeutic acupuncture in China, and the frequent use of medical injection (both intravenous [IV] and intramuscular) in medical clinics, as well as the fact that HCV testing is not part of routine health screening, highlight the potential threat incurred by HCV to public health and the safety of blood supply in China.…”
mentioning
confidence: 99%